Taxes and business philantropy in Armenia - Asatryan, Zareh; Joulfaian, David (ZEW - Leibniz Centre for European Economic Research, 2021)
The majority of countries around the world provide tax incentives for business philanthropy. However, little is known about the responsiveness of businesses to this tax treatment. This paper expands on this scant literature by focusing on the Armenian tax system which provides incentives for business philanthropy. The support takes the form of a deduction capped at a fraction of business receipts. This generates a kink beyond which the marginal tax subsidy drops to zero. Using administrative panel data for the years 2007 through 2017, we find strong evidence of bunching by Armenian firms at the kink, with a sizeable tax elasticity of giving at the intensive margin. The evidence on bunching is robust to whether firms have been audited, and to whether any tax deficiencies are observed. This suggests that the observed response is likely to be real rather than being driven by reporting responses.